Eksplorasi Metode Pembelajaran Seni Gerak dan Tari Dalam Meningkatkan Kepercayaan Diri Anak Usia Dini di RA Amal Ikhlas - Eka Jelita Lubis; Karima; Mauliza Nabila; Rida Khairani; Hilda Zahra Lubis (https://ejournal.insuriponorogo.ac.id/, 2025)
This study aims to explore the method of learning movement and dance arts in increasing the self-confidence of early childhood children at RA Amal Ikhlas, Jalan Cemara, Percut Sei Tuan, Medan. The study was conducted on 10 girls in group B. The method used was a qualitative approach with a case study research type. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that learning movement and dance arts can increase children's courage in expressing themselves, appearing in public, and interacting socially. With a fun and participatory approach, children become more confident in their activities in the school environment. This study recommends the integration of movement and dance arts as part of the routine learning program at RA.